Comparison of incidence of repositioning surgery to correct misalignment with three toric intraocular lenses. Issue 4 (July 2020) - Oshika, Tetsuro; Fujita, Yoshifumi; Hirota, Atsushi; Inamura, Mikio; Inoue, Yasushi; Miyata, Kazunori; Miyoshi, Teruyuki; Nakano, Shinichiro; Nishimura, Tomohisa; Sugita, Toru
Purpose: To compare the incidence of re-orientating surgery to improve misalignment of three models of acrylic toric intraocular lenses: AcrySof toric intraocular lens (Alcon Laboratories, Inc.), TECNIS toric intraocular lens (Johnson & Johnson Vision, Inc.) and HOYA 355 toric intraocular lens (HOYA). Methods: In this retrospective, multicenter case series, medical charts were reviewed for collecting data on realignment surgery of toric intraocular lenses at 10 ophthalmic surgical sites in Japan. Results: Over all, intraocular lens repositioning surgery was conducted in 89 of 9430 eyes (0.944%) at an average of 10.5 ± 9.7 days after the initial cataract surgery. The incidence was 0.213% (11/5155), 1.797% (62/3451) and 1.942% (16/824) with AcrySof, TECNIS and HOYA toric intraocular lenses, respectively. The incidence was significantly lower with AcrySof than with other two brands of toric intraocular lenses ( p < 0.0001). In those eyes which underwent reorientation surgery, the amount of misalignment was 26.4 ± 21.9°, 29.7 ± 15.4° and 28.1 ± 20.7° with AcrySof, TECNIS and HOYA toric intraocular lenses, respectively; there was no significant difference among groups ( p = 0.821). The repositioning surgery significantly reduced misalignment in all three groups. Conclusion: The rotational stability was considerably different among toric intraocular lenses of different manufacturers. The incidence of repositioning surgery was significantly lower with AcrySof than with TECNIS and HOYA toric intraocular lenses.